Affordances of home drinking in accounts from light and heavy drinkers. (March 2022) - MacLean, Sarah; Room, Robin; Cook, Megan; Mugavin, Janette; Callinan, Sarah
Abstract: Home drinking contributes substantially to health harms associated with alcohol consumption. Drawing on practice theory and new materialism, we argue that drinking is a social practice that allows particular sets of effects, or affordances, when it takes place in a person's home. Qualitative interviews were conducted by telephone with 40 Australian adult home drinkers, of whom 20 drank at a level designated as low risk and 20 at a level which exposed them to a higher likelihood of harm. Our analyses identified four substantive affordances of home drinking practice. The first two concern transformations of home life. Home drinking allowed both celebration and smoothing of dissatisfaction with domestic relationships. Through producing subtly different affective states at home compared to in other locations, drinking practice rendered domestic settings home-like: as places of comfort and respite. The second two affordances of home drinking concern how home as a place acts in the co-constitution of drinking patterns. This entailed routinising alcohol consumption alongside other home-based practices and loosening constraints on intoxication. Importantly for our argument, each of these operated with greater intensity for participants who drank at a heavier level than for those who drank more moderately. For example, heavy drinkers expressed a greater imperative to alter relationships and affective states at home and emphasised how being at home produced opportunities for, and removed obstacles to, heavy drinking. We show that home drinking is patterned with other activities and entwined in domestic wellbeing and the emergence of home as a space of privacy, autonomy and relaxation for Australians in our study sample. Understanding home drinking as deeply embedded in the constitution of contemporary western domestic life helps to explain heavy alcohol consumption in these settings. It also supports the need for targeted public health responses such as restrictions on home delivery of alcohol. Highlights: Home drinking is a distinct social practice, with specific affordances or effects. Drinking can smooth relationships and produce an affective sense of being at home. For some, being at home facilitates regular and heavy consumption. Effects of home as a place operate particularly intensely for heavier drinkers. Understanding impacts of place on drinking supports public health responses.